Answer:
The function is increasing from x = 0 to x = 1
Explanation:
Given that :
x g(x)
-2 2
-1 -3
0 2
1 17
The true statement for the given function is:
The function is increasing from x = 0 to x = 1
As we can see from the given function, when x = 0 the corresponding value of the function is 2 but when x = 1 the corresponding value is 17. There is a increase of 15.
i.e → 2 + 15 = 17
From the other options:
The function is increasing from x = −2 to x = −1 ;
NO!, Here the function is decreasing from -2 to -1 because there is a decrease of 5 i.e 2 - 5 = -3
The function is decreasing from x = −1 to x = 0.
when x = -1 ; the function is -3 ; when x = 0 ; the function is 2 . We can see a progressive impact that the function is increasing and not decreasing. The function increases with 5 i.e -3 + 5 = 2
The function is decreasing from x = 0 to x = 1.
It is clear and obvious that the function is increasing when x = 0 to when x = 1